Antecedents of Iphone Product Purchase Decision at Medan Area University Students - Sari Bulan Tambunan; Adelina Lubis; Muslim Wijaya (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study aims to influence the purchasing decisions of iPhone products for students at Universitas Medan Area. The type of research used is explanatory with a quantitative approach. The population in this study were students of Universitas Medan Area who used Iphone smartphones totaling 965 people. The number of samples is 90 respondents using purposive sampling and data collection methods using questionnaires. The data analysis used is Multiple Linear Analysis. Based on the results of the t test, it can be explained that the price, product quality, and lifestyle partially have a significant effect on the iPhone smartphone purchase decision on Universitas Medan Area students. The results of the coefficient of determination analysis can be explained that the price, product quality and lifestyle influence the decision to buy Iphone for students at Universitas Medan Area.